Lontar Tutur Brahma Sapa dan Lontar Dewa Tatwa sebagai Acuan Pemertahanan Tradisi Manak Salah, di Desa Adat Padangbulia, Buleleng, Bali, Indonesia - Luh Putu Sri Ariyani; Nengah Bawa Atmadja; Tuty Maryati; Muhammad Rosyihan Hendrawan (Center for Research and Development of Religious Literature and Heritage, 2023)
Padangabulia Traditional Village is the only village in Bali that maintains the manak salah tradition. Even though the Provincial Government of Bali officially abolished this tradition in 1951 because it was considered to violate religious, Hindu, legal, and health teachings. It is interesting to study this phenomenon through field research using a qualitative approach to find reasons why they still maintain the tradition of manak salah and the rituals that accompany it. Interviews with traditional and religious leaders in Padangbulia village complimented the main data. The results of the study indicated that the maintenance of the tradition of manak salah in this village was legitimized by Lontar Tutur Brahma Sapa and Lontar Dewa Tatwa. These two lontars are sacred texts that are believed to be true. Lontar Tutur Brahma Sapa emphasized thatkembar buncing, male and female twins are wrong because Lord Brahma cursed it. The binarism between humans versus animals reinforces this. Married couples with more than one male and female child were identical to animals. This condition causes contamination of purity or leteh in humans. The Tri Hita Karana ideology outlines that humans are united with fellow human beings and the natural environment and God/gods who reside in temples. This idea causesleteh in humans and spreads to the natural environment and temples. Lontar Dewa Tatwa explains that impurities must be cleaned through a purification ritual, includingmelastito the sea. Whenever there is a case of manak salah, they will implementmelasti at the Buleleng Harbor beach. This creates a unique tradition: this traditional village does not perform melasti at every Nyepi Day celebration but only when there is a manak salah. This ritual not only has a religious-magical function but also has a social function. These functions strengthen Lontar Tutur Brahma Sapa'sposition in maintaining the manak salah tradition.